Mechanical properties of carbon-based epoxy grout as infill material for steel pipeline repair - Lim, Kar Sing; Doh, Shu Ing; Chin, S. C.; Cheng, Hock Tian; Nordin, Yahya; Norhazilan, Md Noor; Libriati, Zardasti (2019)
The industry nowadays is incorporating the composite repair system for repairing pipelines rather than the conventional steel repair. The mechanism of this repair method usually consists of three components which are the composite wrap, infill material and the adhesive. However, there have been very little researches on the function of the infill in the repair mechanism. This work is concerning the enhancement of the performance or the strength properties of the infill material in pipeline repair by reinforcing the putty with carbon-based nano fillers which are graphene nanoplatelets (Gnp) and carbon nanotubes (CNT). The enhancement of the performance of the infill has been carried out by dispersing the carbon-based nano fillers into epoxy resin with a three roll mill. In the mechanical properties testing, it is found that the both carbon-based nano fillers are effective material to improve the tensile strength of the epoxy grout. However, the modified samples in the compressive properties test show a contrast to the tensile test. All the modified samples exhibit a lower compressive strength than the control sample and the milled down sample. In conclusion, graphene nanoplatlets and CNT can be a very good material to enhance the mechanical properties of epoxy grout, however, with this specific brand of epoxy grout that contains steel filler in the resin, the CNT only improve the tensile properties but the compressive properties of the epoxy grout decrease as compared to the control sample.